Molecular analysis of BCR-ABL1 fusion transcripts in acute leukemia patients in Southern Odisha, India - Sabat, Sheetal; Naik, Aparupa; Purohit, Prasanta; Bholo, Snehal; Parida, Chinmayee; Patro, Manoj Kumar; Behera, Samira Kumar (European Journal of Clinical and Experimental Medicine, 2026)
Introduction and aim. The occurrence of BCR-ABL1 fusion transcript in acute-leukemia cases are limited and is characterized with various subtypes. This study was based on investigation of the BCR-ABL1 fusion transcript in acute-leukemia cases in a tertiary care hospital. Material and methods. This cross-sectional study was carried out in suspected cases of acute leukemia. Cases were analyzed for complete blood counts, peripheral smear, bone marrow and flow-cytometry for the diagnosis of acute-leukemia. Additionally, diagnosed cases were investigated for BCR-ABL1 fusion transcript by PCR amplification using reverse transcriptase enzyme followed by documentation. Results. Approximately 55 acute leukemia cases included, diagnosed by flow cytometric analysis. Analysis of the BCR-ABL1 fusion-transcript in 55 cases showed its occurrence in only 2 cases, where one case with the B-ALL was characterized with e1a2 subtype and a other case with AML was characterized with the e13a2 subtype. Conclusion. The BCR-ABL1 fusion transcript in acute-leukemia cases was found in 3.64% (2/55) of cases. The diagnosis of BCR-ABL1 fusion transcript in acute-leukemia cases is important for its poor prognosis, as well as calls for the use of ABL tyrosine kinase inhibitors. The diagnosis of BCR-ABL1 fusion-transcript in acute leukemia cases in a tertiary health care facility will be helpful for better treatment of patients in the study area.